math
posted by avincent .
first was w=Cr^2
solve for r
I came up with r=sqrt of C/w
Now I have imputed numbers that were provided to come up with the equation 3,963=sqrt c/100
I squared both sides to come up with 15,705,369=c/100
Now I am stuck. Trying to solve for C. Am I on the right track?

multiply both sides by 100
Respond to this Question
Similar Questions

MATH
I need to simply this equation, but I got stuck. h/(4sqrt(16+h)) = y First, I multiplied (4+sqrt(16+h)/(4+sqrt(16+h) to both sides, and I ended up with h(4+sqrt(16+h)/h. Is this correct? 
Algebra
Solve for s: h=(square root of 3)times s/2 and solve for h V= (pi)r squared h / 3 Solve for s: h=(square root of 3)times s/2 Multiply both sides by 2. 2h = (sqrt 3)*s*2/2 which cancels the 2 on the right. 2h = (sqrt 3)*s Now divide … 
math,algebra,help
Directions are simplify by combining like terms. x radiacal 18 3 radical 8x^2 can someone show me how to do these types of problems. thanks I cant determine the second term. For the first, I think you meant x sqrt(18) which reduces … 
algebra
Can someone please help me with this one? 
math,help,algebra I
I need help can someone help me get unstuck and let me know if i am correct.thank you. solve by completing the square. 4x^2+2x3=0 this is what i am doing: i used the quadratic equation. so where i am is in this step: x = (2 (+) … 
math,correction
simplify: sqrt ((7)/(100)) my work: 7 = 1sqrt (7) 100= 10 sqrt (1) (1)/(10) sqrt (7) my answer: (sqrt (7))/(10) Your answer is right but your statements: 7 = 1sqrt (7) 100= 10 sqrt (1) make no sense. how can sqrt(7)=7 ? 
Math Help please!!
Could someone show me how to solve these problems step by step.... I am confused on how to fully break this down to simpliest terms sqrt 3 * sqrt 15= sqrt 6 * sqrt 8 = sqrt 20 * sqrt 5 = since both terms are sqrt , you can combine … 
Math
Could someone please check my work on these word problems? 
Algebra
Could you please check my work on these word problems? 
Surds
Solve in the exact form. (sqrt of 4x+1)+(sqrt of x+1)=2 Someone showed me to do this next: Square both sides..so.. 4x+1+2((sqrt of 4x+1)•(sqrt of x+1))=4 I do not understand where the 2 come from ..and why do we need to multiply …